The pursuit of happiness and the American regime political theory in literature - Amato, Elizabeth (Politics, literature, and film, 2018)
This book explores happiness research and liberal theory. It treats four American novelists as political thinkers through close textual analysis of their novels. This book concludes that friendship is the real basis of happiness and that it is an alternative to the individualistic pursuit of happiness.